Systematization of threats to the enterprise personnel security under conditions of global instability (Economics and region, 2025)
This research addresses critical challenges facing personnel security in Ukrainian enterprises amid unprecedented global instability and military confrontation. The study develops a comprehensive multilevel systematization framework identifying and analyzing threats operating across global, national, and organizational dimensions while highlighting their synergistic interactions. Contemporary enterprises face compound vulnerabilities from geopolitical turbulence manifested through targeted talent extraction from strategic sectors, transnationalization of labor markets intensifying competition for specialists, and divergence of digital competencies creating gaps between international requirements and actual skill levels. The investigation reveals alarming mass labor emigration patterns, with over six million displaced Ukrainian workers fundamentally disrupting workforce demographics. National-level threats include vocational training degradation, demographic crisis with negative population growth, shadow economy expansion, labor market militarization, and institutional dysfunction in personnel management frameworks. At the microeconomic level, enterprises confront acute personnel shortages, cultural-value transformations altering motivation hierarchies, internal security crises involving espionage and sabotage, psychoemotional burnout from prolonged stress, organizational disengagement including quiet quitting, and digital risks compromising information security. The research identifies integral threats emerging at operational intersections, including structural deformation of human capital, value-cultural fragmentation across generations, and systemic vulnerabilities at boundaries between global actors and national frameworks. Findings demonstrate conventional isolated approaches prove insufficient for contemporary challenges. The investigation argues for integrated management strategies synchronizing state institutions, business entities, and civil society while incorporating early warning systems. Practical implications emphasize adaptive management models, security-oriented corporate cultures, and professional cohesion amid multifactor disruptions, providing actionable frameworks for strengthening organizational resilience during military and post-conflict periods.
Keywords: enterprise personnel security; human capital; global risks; threats; economic security; management